Addressing Death Anxiety in Terminally III Patients: A Review of Current Interventions and Future Directions - Roza, Defia; Sasmita, Heppi; Fadriyanti, Yessi (Frontiers on Healthcare Research, 2024)
particularly those facing chronic or terminal illnesses. Understanding the factors influencing death anxiety and the effectiveness of interventions is crucial for improving patient care and outcomes. This review aims to explore the psychological, social, and environmental factors contributing to death anxiety and evaluate the effectiveness of interventions designed to mitigate this anxiety. Additionally, it seeks to identify research gaps and provide recommendations for future studies. Methods: A literature search was conducted, resulting in the inclusion of ten studies focusing on different populations, including COVID-19 patients, elderly individuals in nursing homes, and terminally ill cancer patients. The studies employed various methodologies such as correlational studies, path analysis, conceptual analysis, retrospective analysis, comparative studies, and randomized controlled trials. Data were synthesized to identify common themes, methodological quality was assessed, and findings were compared and contrasted. Results: Psychological interventions, including cognitive-behavioral therapy (CBT), well-being therapy (WBT), and spiritual care programs, were found to be effective in reducing death anxiety. The design of healthcare environments also significantly impacted death anxiety, with well-designed palliative care settings providing substantial benefits. Holistic approaches addressing psychological well-being, meaning in life, self-care, and social capital were essential in managing death anxiety, especially among the elderly. However, several research gaps were identified, including the need for long-term studies, comparative effectiveness research, culturally sensitive interventions, and the potential of technology-based interventions. Conclusion: The review highlights the importance of integrated, holistic, and culturally sensitive approaches to managing death anxiety. By addressing the identified research gaps and implementing the recommended strategies, healthcare systems can enhance the quality of care for patients facing death anxiety, leading to improved patient outcomes and more compassionate end-of-life care.